Efficacy of Venetoclax and Dexamethasone in Refractory IgM Primary Plasma Cell Leukemia with t(11;14) and TP53 Mutation: A Case Report and Literature Review - Valliani, Salimah; Ali, Mir; Mahmoo, Omar; Hinduja, Sanjay; Chen, Calvin K.; Damon, Lloyd; Abdulhaq, Haifaa (Case Reports in Hematology, 2020)
Primary plasma cell leukemia (pPCL) is an uncommon disease. IgM multiple myeloma (MM) is an infrequent subtype that accounts for less than 1 percent of MM cases. IgM pPCL is quite rare with only a few cases published to date. We describe a case of a patient with IgM pPCL who initially presented with hyperviscosity syndrome requiring urgent plasma exchange. His bone marrow biopsy demonstrated t(11;14). He progressed on proteasome inhibitors, immunomodulating agents, and other chemotherapy medications but later achieved very good partial response (VGPR) to venetoclax and dexamethasone. Given the poor prognosis of pPCL, further studies using venetoclax alone or in combination with other novel agents as first-line treatment options are warranted particularly in patients with t(11;14).